Role of Regular ANC Visits and Feeding Practices in Preventing Malnutrition in Children Under Five Years Old - Melake, Issayas Ghirmay; Mirach, Isaias Tesfu; Andom, Hagos (International Journal of Child Health and Nutrition, 2019)
Introduction: Malnutrition has a significant impact on global disease for the majority of children worldwide, by being responsible for almost half of the deaths of children under the age of five especially in the developing countries including Eritrea. However, there is no clear information on the role of antenatal care and feeding practices in preventing malnutrition. Therefore, assessing the role of antenatal care visit and feeding practices in preventing malnutrition is of vital importance. Objective: To assess the role of regular ANC visit and feeding practices in preventing malnutrition among children aged 0-59 months, who visited Orotta National Pediatric Referral Hospital from 31st August – 30th September, 2016. Methodology: A cross-sectional, Hospital based study was carried out. Data were collected from mothers (caretakers) using semi-structured questionnaire developed for the purpose. Moreover, anthropometric measurement of the subjects was taken. Data was and entered to the computer and analyzed using SPSS version 20 and p-value <0.05 at 95%CI was considered as statistically significant. Results: The main associated factors of stunting were found to be the frequency of breastfeeding and antenatal care visit. Underweight was associated with weaning of breastfeeding. Frequency of breastfeeding and weaning of breastfeeding were the only variables associated with wasting. Conclusion and Recommendation: Malnutrition remains a major health problem among children aged 0-59 months. Hence, interventions regarding regular antenatal care visits and feeding practices are highly suggested to be given special attention.